2021
DOI: 10.1038/s41598-020-79531-4
|View full text |Cite
|
Sign up to set email alerts
|

Baseline data report of the China Dialysis Outcomes and Practice Patterns Study (DOPPS)

Abstract: The number of patients on hemodialysis (HD) is rapidly increasing in China. As an Asian country with a large number of HD patients, understanding the status of Chinese HD patients has a special significance. We reported here the baseline data for China Dialysis Outcomes and Practice Pattern Study Phase 5 (DOPPS5). The DOPPS is an international prospective, observational cohort study. Patients were restricted to the initial sample of patients who participated in China DOPPS5. We summarized the baseline demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
1
35
1
Order By: Relevance
“…DOPPS China randomly selected an average of 30 patients from 15 dialysis facilities in each city of Beijing, Shanghai, and Guangzhou. This was described in our previous study [ 24 – 26 ]. There were 1427 patients participated in China DOPPS5 (2012–2015).…”
Section: Methodsmentioning
confidence: 86%
“…DOPPS China randomly selected an average of 30 patients from 15 dialysis facilities in each city of Beijing, Shanghai, and Guangzhou. This was described in our previous study [ 24 – 26 ]. There were 1427 patients participated in China DOPPS5 (2012–2015).…”
Section: Methodsmentioning
confidence: 86%
“…For adult HD patients, KDIGO suggests that ESAs therapy is used to avoid having the Hgb concentration fall below 90 g/L by starting erythropoietin therapy when the Hb is between 90–100 g/L in 2012 [ 19 ]. Our study showed that 11.76% of patients in the HIV-HD group and 5.71% of patients in the HD group had Hgb < 90 g/L, compared with 18.8% patients in China Dialysis Outcomes and Practice Patterns Study (DOPPS) [ 20 ]. The reason for the lower prevalence of Hgb < 90 g/L maybe include younger age, shorter dialysis vintage, higher percentage of males and higher dialysis frequency in enrolled patients in our study (Table 4 ) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that 11.76% of patients in the HIV-HD group and 5.71% of patients in the HD group had Hgb < 90 g/L, compared with 18.8% patients in China Dialysis Outcomes and Practice Patterns Study (DOPPS) [ 20 ]. The reason for the lower prevalence of Hgb < 90 g/L maybe include younger age, shorter dialysis vintage, higher percentage of males and higher dialysis frequency in enrolled patients in our study (Table 4 ) [ 20 ]. There was no significant difference in Hgb and ferritin between HIV-HD and HD patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…DOPPS China randomly selected an average of 30 patients from 15 dialysis facilities in each city of Beijing, Shanghai, and Guangzhou. This was described in our previous studies 16,17 . Inclusion criteria for participants were age ≥18 years, treated at an in‐center dialysis clinic and receiving chronic, maintenance HD.…”
Section: Methodsmentioning
confidence: 99%
“…This was described in our previous studies. 16,17 Inclusion criteria for participants were age ≥18 years, treated at an in-center dialysis clinic and receiving chronic, maintenance HD. Exclusion criteria: patients <18 years, treated with a home-based dialysis modality or receiving HD for acute kidney injury.…”
Section: Study Design and Subjectsmentioning
confidence: 99%